Pengaruh Hafalan Al-Qur’an terhadap Ketenangan Jiwa dalam Perspektif Tasawuf Psikoterapi di Pondok Pesantren Darussalam Purwokerto - Shofa Nurlayly, Kamalia (Theofani: Journal of Islamic Studies and Scholarly Discourse, 2025)
This study aims to examine the influence of Qur’anic memorization (tahfidz) on students’ inner peace, viewed through the lens of Sufi psychotherapy. Conducted at the Darussalam Islamic Boarding School in Purwokerto, this research applied a qualitative approach. Data were collected through in-depth interviews and participatory observation involving tahfidz students and their mentors. The findings reveal that memorizing the Qur’an functions not only as a cognitive and religious activity but also as a potent psychospiritual practice. The tahfidz process fosters inner peace through spiritual closeness to God, contemplation of verses, improved concentration, disciplined routine, and the cultivation of gratitude and optimism. Students who consistently engaged in tahfidz demonstrated greater emotional stability, calmness in dealing with challenges, patience, and self-control. These findings support the Sufi concepts of tazkiyatun nafs and muraqabah as essential foundations for psychological recovery. The boarding school environment, which promotes spiritual discipline, plays a significant role in shaping students’ emotional well-being through Qur’anic memorization.